2008
DOI: 10.1073/pnas.0708598105
|View full text |Cite
|
Sign up to set email alerts
|

A simple and exact Laplacian clustering of complex networking phenomena: Application to gene expression profiles

Abstract: Unraveling of the unified networking characteristics of complex networking phenomena is of great interest yet a formidable task. There is currently no simple strategy with a rigorous framework.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…A separation between DLBCL and FL/B-CLL is clearly apparent in the first two components, whereas FL and B-CLL can be distinguished in the third component. From this unsupervised KODAMA analysis, we may conclude that the lymphoma data consist primarily of two classes (DLBCL and FL/B-CLL) and that FL and B-CLL are secondary classes, confirming the results obtained in a previous study (5). KODAMA performed with SVM shows a clear separation of the three different malignancies, as does LLE and at variance with PCA and ISOMAP (Fig.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…A separation between DLBCL and FL/B-CLL is clearly apparent in the first two components, whereas FL and B-CLL can be distinguished in the third component. From this unsupervised KODAMA analysis, we may conclude that the lymphoma data consist primarily of two classes (DLBCL and FL/B-CLL) and that FL and B-CLL are secondary classes, confirming the results obtained in a previous study (5). KODAMA performed with SVM shows a clear separation of the three different malignancies, as does LLE and at variance with PCA and ISOMAP (Fig.…”
Section: Resultssupporting
confidence: 77%
“…Therefore, the use of data mining methods is an intrinsically risky activity that can easily lead to the discovery of meaningless patterns. The reliability of a clustering solution can be verified a posteriori by evaluating the predictive accuracy of a supervised classifier by repeatedly leaving out one or a few randomly selected samples as a "test set," whereas the remaining data objects are used as a "training set" (cross-validation) (4)(5)(6).…”
mentioning
confidence: 99%
“…We first set a ceiling (16,000) and a floor (100) for the intensities and then filter those genes with max/min5or maxmin500so that the informative genes are retained according to a general procedure and a base 10 logarithmic transformation is applied at the end [26]. Here max and min mean the maximum and minimum gene expression values in all the samples, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Spectral clustering can be generally solved by seeking the Fiedler vector of the Laplacian matrix [22,26]. The resulting vector sums to zero and the norm equals to one.…”
Section: Resultsmentioning
confidence: 99%
“…There are numerous methods on clustering and classification; see Speed (2003) among others for the analysis of microarray data. Recently, Kim et al (2008) suggested a simultaneous approach to clustering and classification. In microarray data, one may be interested in two ways of inference.…”
Section: Clustering and Classificationmentioning
confidence: 99%